2007
DOI: 10.1039/b703690f
|View full text |Cite
|
Sign up to set email alerts
|

An efficient microwave-assisted green transformation of cellulose into levoglucosenone. Advantages of the use of an experimental design approach

Abstract: The microwave-assisted pyrolysis of cellulose towards its conversion into levoglucosenone is reported. An experimental design approach was used to find the variables involved in this transformation. Using this approach we established the optimal conditions to obtain the maximum yield of product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 23 publications
1
57
0
2
Order By: Relevance
“…Theoretically, microwaves could heat biomass materials at very high rates due to the volumetric heating and this process is likely to offer significant efficiencies over conventional resistively heated reactors. There have been few reports on microwave catalytic pyrolysis in the literature [50,51], however non-catalytic microwave pyrolysis of biomass materials such as cellulose [52][53][54] and lignin/wood [51,55,56] [57] report the microwave pyrolysis of corn stover and the bio-oils properties were determined. Stover was heated for 40 min at 600 W but no heating rate was recorded.…”
Section: Challenges With Catalytic Fast Pyrolysismentioning
confidence: 99%
“…Theoretically, microwaves could heat biomass materials at very high rates due to the volumetric heating and this process is likely to offer significant efficiencies over conventional resistively heated reactors. There have been few reports on microwave catalytic pyrolysis in the literature [50,51], however non-catalytic microwave pyrolysis of biomass materials such as cellulose [52][53][54] and lignin/wood [51,55,56] [57] report the microwave pyrolysis of corn stover and the bio-oils properties were determined. Stover was heated for 40 min at 600 W but no heating rate was recorded.…”
Section: Challenges With Catalytic Fast Pyrolysismentioning
confidence: 99%
“…The highest LGO yield reached 34 wt% from microcrystalline cellulose impregnated with 2% phosphoric acid, or 17.5 wt% from birch wood impregnated with 2.5% phosphoric acid. Other studies also confirmed the promising catalytic selectivity of the phosphoric acid on the LGO production (Sarotti et al, 2007;Fu et al, 2008b;Nowakowski et al, 2008). Furthermore, Dobele et al (2005) reported that the pretreatment of cellulose/biomass with adsorption of Fe 2 (SO 4 ) 3 provided another way to prepare LGO with high purity, but the selectivity of the Fe 2 (SO 4 ) 3 on the LGO was a little lower than the phosphoric acid.…”
Section: Levoglucosenonementioning
confidence: 61%
“…O grupo de Spanevello explorou o uso dessa substância em síntese assimétrica. 43 O seu uso como reagente químico tem basicamente três grandes estratégias. A mais comum é a transformação radical da sua estrutura, por meio de processos químicos ou bioquímicos , como pode ser visto no Esquema 9.…”
Section: O Uso De Biomassa Renovável No Contexto Atualunclassified